Cathepsin D Polymorphism C224T in Childhood-Onset Neurodegenerative Disorders: No Impact for Childhood Dementia - Kettwig, Matthias; Ohlenbusch, Andreas; Jung, Klaus; Steinfeld, Robert; Gärtner, Jutta (Journal of Pediatric Genetics, 2018)
Compromised lysosomal functioning has been identified as a major risk factor for neurodegenerative disorders such as Alzheimer's and Parkinson's diseases. Furthermore, the association between a defined cathepsin D (CTSD) polymorphism and a higher risk of sporadic Alzheimer's disease has been established for particular populations. Here, we analyzed 189 children with rare neurodegenerative disease for carrying the T-allele by polymerase chain reaction-restriction fragment length polymorphism. We found no statistical differences in genotype and allele frequencies between the neurodegenerative group and European descent participants of genetic studies using the Cochran–Armitage's trend test. In contrast to adult-onset neurodegenerative diseases, analysis of clinical datasets of children carrying the T-allele did not demonstrate differences to the general disease group.
Keywords: lysosomal dysfunction; childhood dementia; neurodegenerative disorders; cathepsin D polymorphism